2017
DOI: 10.1017/s003060531700076x
|View full text |Cite
|
Sign up to set email alerts
|

Robust monitoring of the Eurasian lynxLynx lynxin the Slovak Carpathians reveals lower numbers than officially reported

Abstract: The Eurasian lynx Lynx lynx population in the Carpathian Mountains is considered to be one of the best preserved and largest in Europe and hence is a source for past and current reintroduction projects in central Europe. However, its status in Slovakia has been reported to the European Commission on the basis of hunters´ reports and expert estimates that have never been validated by a robust scientific approach. We conducted the first camera-trapping surveys to estimate the density of Eurasian lynx in Slovakia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 24 publications
(35 reference statements)
5
38
0
Order By: Relevance
“…When examining densities across study areas in the French Jura mountains, we found spatial variation between the three counties, with Doubs area having the lowest densities, Ain the highest densities, and Jura intermediate densities. Our density estimates were of similar magnitude to other lynx populations in Europe: 1.47 and 1.38 lynx/100 km 2 in the Northwestern Swiss Alps (Pesenti & Zimmermann, ), 0.58 (Štiavnica mountains) and 0.81 individuals/100 km 2 (Velká Fatra National Park) in Slovakia (Kubala et al, ) and 0.9 individuals/100 km 2 in the Bavarian Forest National Park in Germany (Weingarth et al, ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…When examining densities across study areas in the French Jura mountains, we found spatial variation between the three counties, with Doubs area having the lowest densities, Ain the highest densities, and Jura intermediate densities. Our density estimates were of similar magnitude to other lynx populations in Europe: 1.47 and 1.38 lynx/100 km 2 in the Northwestern Swiss Alps (Pesenti & Zimmermann, ), 0.58 (Štiavnica mountains) and 0.81 individuals/100 km 2 (Velká Fatra National Park) in Slovakia (Kubala et al, ) and 0.9 individuals/100 km 2 in the Bavarian Forest National Park in Germany (Weingarth et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…While Kubala et al () and Pesenti and Zimmermann () used SCR models, (Weingarth et al, ) used standard capture–recapture models with HMMDM to estimate densities, which makes them difficult to compare (Gerber, Karpanty, & Kelly, ). Indeed, in other carnivore studies, the use of HMMDM also produced similar density estimates to SCR models (Pesenti & Zimmermann, ), while in others, including ours, the SCR estimates were closer to the MMDM estimates (Obbard et al, ) or intermediate between the MMDM and HMMDM estimates (Reppucci, Gardner, & Lucherini, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this population has not been exempted from intense direct persecution that left around 100 individuals in Romania by 1930 (Kratochvil, ), and probably similar numbers in the Slovakian part (Hell & Slamečka, ). The protection of the species in both countries in the 1930s allowed a significant recovery of the population with around 500 individuals in Romania by 1950 and 400–500 in Slovakia in the period 1960–1990 (Kubala et al, ). Similar scenarios with western fragmented and bottlenecked populations due to continued human pressure during the Holocene versus more contiguous and stable ranges in the east have also been postulated for other carnivore species such as wolf and brown bear in Europe (Adamec et al, ; Hindrikson et al, ; Pilot et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A primary anthropogenic factor is possible changes in tolerance as a function of levels of depredation (Harmsen et al, 2017;. Ecological factors include prey availability, interspecific and intraspecific competition, mortality, seasonal changes in home range size, tenure and turnover due to interspecific and intraspecific competition or displacement, and the presence of dispersers (Durant, 1998;Fabiano, 2013;Kubala et al, 2017;Marker, Dickman, et al, 2008;Melzheimer et al, 2018;Swanson et al, 2014).…”
Section: Density Estimationmentioning
confidence: 99%